2020
DOI: 10.1109/ojap.2020.3038001
|View full text |Cite
|
Sign up to set email alerts
|

Meshed High-Impedance Matching Network-Free Rectenna Optimized for Additive Manufacturing

Abstract: Additive manufacturing using direct-write or screen printing represent low-waste methods for fabricating antennas on low-cost flexible substrates. To realize rectennas using low-resolution printing methods, high-impedance antennas with simple printable geometries are required. This article proposes an electrically-small (0.212×0.212λ 2 ) folded dipole antenna design with a scalable impedance for directly matching energy harvesting rectifiers. The antenna is demonstrated in a high-efficiency sub-1 GHz rectenna,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Fig. 15 shows the test setup of the proposed antenna, the same setup from [10] and [51]. The communications port was terminated using a 50Ω SMA termination.…”
Section: Rectenna Measurementsmentioning
confidence: 99%
“…Fig. 15 shows the test setup of the proposed antenna, the same setup from [10] and [51]. The communications port was terminated using a 50Ω SMA termination.…”
Section: Rectenna Measurementsmentioning
confidence: 99%
“…1-c. The antenna was fabricated using direct-write dispenser printing using a Voltera V-One printer and flexible silver ink, using the process detailed in [13] and [10]. The antenna was printed on a flexible 75 µm polyimide (Kapton) substrate with r =3.4 and tanδ=0.02.…”
Section: Dual-band Printed Rectenna Designmentioning
confidence: 99%
“…P RF is assumed to be 1 dBm based on the calculated incident power density S=7.4 µW/cm 2 and a receiving antenna gain of 2.1 dBi. By using the gain of a typical λ/2 dipole, the antenna effect as well as the rectification losses are factored in the PCE, enabling holistic evaluation of the rectenna [10]. In Fig 6-b (solid line), it can be observed that in approximately 5 seconds in very close proximity (3-5 cm) from a 446 MHz handheld radio, the rectenna harvests 47.6 mJ.…”
Section: Rectenna Wireless Chargingmentioning
confidence: 99%
See 1 more Smart Citation
“…The designed antennas have been fabricated on a flexible polyimide substrate of 75 µm thickness. Direct-write dispenser printing, recently demonstrated for energy harvesting [33] and IoT antenna prototyping [34], has been utilized to deposit the silver tracks on the organic polymer substrate. The printer used is a commercially-available Voltera V-one printer, intended for rapid and low-cost PCB prototyping.…”
Section: Sensor Fabrication and Measurements A Additively-manufactured Sensors Characterizationmentioning
confidence: 99%